(untitled) (Scientific journal of the Fergana State University, 2023)
The article shows a number of cognitive features of the concept of quantity in Uzbek folk proverbs. Figurative nature of proverbs is not related to explicit or hidden comparisons in them - it is the result of cognitive processes that are manifested in different ways in the cognitive bases of the semantic structure of proverbs of different types. In the proverbs created by mankind, people compare and complete their thoughts about concepts based on one concept and another concept, and ensure that the expressions are figurative. Based on the expression of primary thoughts, he verbalizes secondary, derivative thoughts. Numbers represent several cognitive aspects in addition to their function. The numbers interpreted as a national-cultural indicator are a unique linguistic and cultural sign that expresses the spiritual thinking, worldview, and national mentality of each nation. By studying proverbs in the Uzbek language from this point of view and classifying them on the basis of linguistic and cultural codes, it is possible to create models of Uzbek thought, and to shed light on the mechanisms specific to the linguistic consciousness of the nation.